ANALISIS KESENJANGAN SOPAN SANTUN SANTRI TPA DALAM PENDIDIKAN KARAKTER ISLAM - Chairullah; Aulia Rahmi; Eka Mayasari; Nurliza Zuhra; Muliana (CV. Gerasi Insan Nusantara, 2026)
This research aims to analyze the gap in the politeness of TPA students in the implementation of character education. The background of this research is based on the finding that the polite behavior of TPA students does not fully reflect the character values taught in Islam. This research uses a qualitative approach with a field research type. Data were collected thru interviews, observations, and documentation, then analyzed thru the stages of data reduction, data presentation, and conclusion drawing. The research results show that character education has been implemented thru habituation, the enforcement of regulations, and the provision of advice on the importance of manners to teachers and fellow students. However, this study also found a gap between the values taught and the behavior of students in daily interactions, both toward teachers and fellow peers. The gap is influenced by the child's internal factors, the consistency of habituation, and the impact of the external environment. These findings indicate that character formation cannot be achieved instantly, but rather requires continuity, consistency, and collaboration between TPA (Islamic Education Centers) and parents in reinforcing the internalization of polite values.